Protective effects of soy-isoflavones in cardiovascular disease - Wenzel, U.; Fuchs, D.; Daniel, H. (Hämostaseologie, 2008)
Epidemiological studies indicate that the consumption of soy-containing food may prevent or slow-down the development of cardiovascular disease. In endothelial cells application of a soy extract or a combination of the most abundant soy isoflavones genistein and daidzein both inhibited apoptosis, a driving force in atherosclerosis development, when applied in combination with oxidized LDL or homocysteine. Proteome analysis revealed that the stressorinduced alteration of protein expression profile was reversed by the soy extract or the genistein/daidzein mixture. Only few protein entities that could be functionally linked to mitochondrial dysfunction were regulated in common by both application forms of isoflavones. A dietary intervention with isoflavone-enriched soy extract in postmenopausal women, who generally show strongly increased cardiovascular risk due to diminished estrogen production, led to significant alterations in the steady state levels of proteins from mononuclear blood cells. The proteins identified by proteome analysis revealed that soy isoflavones may increase the anti-inflammatory response in blood mononuclear cells thereby contributing to the atherosclerosispreventive activities of a soy-rich diet. Conclusion: By proteome analysis protein targets were identified in vitro in endothelial cells that respond to soy isoflavones and that may decipher molecular mechanisms through which soy products exert their protective effects in the vasculature.
Keywords: Isoflavone; cardiovascular disease